2012
DOI: 10.1111/j.1365-2885.2012.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of paroxetine, a selective serotonin reuptake inhibitor, in Grey parrots (Psittacus erithacus erithacus): influence of pharmaceutical formulation and length of dosing

Abstract: Paroxetine, a selective serotonin reuptake inhibitor, may be beneficial in the treatment of behavioural disorders in pet birds. The lack of pharmacokinetic data and clinical trials currently limits the use of this drug in clinical avian practice. This paper evaluates the pharmacokinetic properties and potential side effects of single and repeated dosing of paroxetine in Grey parrots (Psittacus erithacus erithacus). Paroxetine pharmacokinetics were studied after single i.v. and single oral dosing, and after rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In a pharmacokinetic study in African grey parrots, 69 it was found that paroxetine had a rapid distribution and elimination after IV administration. Oral administration of paroxetine HCl dissolved in water resulted in a relatively slow absorption with a T max of 5.9 Ϯ 2.6 hours and a low oral bioavailability of 31 Ϯ 15%.…”
Section: Erythropoietinmentioning
confidence: 99%
“…In a pharmacokinetic study in African grey parrots, 69 it was found that paroxetine had a rapid distribution and elimination after IV administration. Oral administration of paroxetine HCl dissolved in water resulted in a relatively slow absorption with a T max of 5.9 Ϯ 2.6 hours and a low oral bioavailability of 31 Ϯ 15%.…”
Section: Erythropoietinmentioning
confidence: 99%
“…A study on pharmacokinetics of paroxetine in gray parrots indicated presence of gender-based differences in plasma concentrations. 45 This emphasizes the need to further study the effects of aforementioned patient parameters on the drug's action. Information from studies in humans and other animals may provide initial clues on whether and how these factors may affect the efficacy and tolerability of a drug in a given situation.…”
Section: Box 2 Checklist For Administering Medication For Behavior Modification In Birdsmentioning
confidence: 99%
“…Moreover, formulation may significantly alter the absorption (and, therefore, clinical efficacy) of drugs as shown in gray parrots, where a commercial suspension of paroxetine resulted in little to no absorption after oral administration compared with a waterbased solution of paroxetine. 45 Similarly, challenges may be encountered with intake of medication because of an owner being unable to administer the drugs and/or the bird resisting medication (eg, due to taste aversion of bitter-tasting drugs [Fig. 3]).…”
Section: Box 2 Checklist For Administering Medication For Behavior Modification In Birdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paroxetine and fluoxetine are the two SSRIs that are used infrequently in avian practice, with paroxetine having been shown to decrease impulsive behaviour in pigeons (Wolff and Leander 2002). Evaluation of paroxetine pharmacokinetics in parrots supports its role as a potential agent for managing compulsive FDB in avian patients, but demonstrated unreliable absorption of standard commercial preparations, indicating that current human formulations are of limited benefit (Van Zeeland and others 2013). Fluoxetine has been demonstrated to reduce feather picking initially, but a large proportion of treated birds relapsed subsequently (Mertens 1997).…”
Section: Managing Behavioural Causesmentioning
confidence: 99%